PEG-coated gold nanoparticles attenuate β-adrenergic receptor-mediated cardiac hypertrophy - Qiao YH (Dove Medical Press, 2017)
Yuhui Qiao, Baoling Zhu, Aiju Tian, Zijian Li Department of Cardiology, Institute of Vascular Medicine, Peking University Third Hospital, Key Laboratory of Cardiovascular Molecular Biology and Regulatory Peptides, Ministry of Health, Key Laboratory of Molecular Cardiovascular Sciences, Ministry of Education and Beijing Key Laboratory of Cardiovascular Receptors Research, Beijing, People’s Republic of China Abstract: Gold nanoparticles (AuNPs) are widely used as a drug delivery vehicle, which can accumulate in the heart through blood circulation. Therefore, it is very important to understand the effect of AuNPs on the heart, especially under pathological conditions. In this study, we found that PEG-coated AuNPs attenuate β-adrenergic receptor (β-AR)-mediated acute cardiac hypertrophy and inflammation. However, both isoproterenol, a non-selective β-AR agonist, and AuNPs did not induce cardiac function change or cardiac fibrosis. AuNPs exerted an anti-cardiac hypertrophy effect by decreasing β1-AR expression and its downstream ERK1/2 hypertrophic pathway. Our results indicated that AuNPs might be safe and have the potential to be used as multi-functional materials (drug carrier systems and anti-cardiac hypertrophy agents). Keywords: AuNPs, cardiac hypertrophy, β-adrenergic receptor, ERK1/2 signaling pathway